A Study of the Optical Properties of Sm-doped ZnWO4 Synthesized by Hydrothermal Method - Hung, Nguyen Manh; An, Nguyen Manh; Minh, Nguyen Van (Communications in Physics, 2012)
The ZnWO4:Sm3+ compounds were prepared by hydrothermal method and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman scattering, absorption and photoluminescent (PL) techniques. This rare earth material presents high orange luminescence intensity under UV radiation. The excitation spectra of the compound presented broad bands arising from ligand-to-metal charge transfer (LMCT) (O®W and O®Sm3+) and narrow bands from 4f-intraconfigurational transitions. The emission spectra exhibited the 4G5/2®6HJ (J = 5/2, 7/2, 9/2 and 11/2) transition (direct excitation), for the system doped with Sm3+, while a broad band assigned to the LMCT (O®W) is observed when the excitation is monitored on the O®W LMCT state.